Moral neoestoica alegorizada en El Criticón de Gracián - Sagrario López Poza (Mélanges de la Casa de Velázquez)
El Criticón, a work by Baltasar Gracián published in three parts (1651, 1653 and 1657)—and considered by critics to be its author’s masterpiece and one of the high points of Spanish literature—has been ascribed to various different genres, among them the Byzantine novel and Menippean satire. This paper seeks to highlight the importance of the mixture of genres in which the author composed the work, in the light of his arguments in Agudeza y arte de ingenio (1648) where he presents «feigned compound acuity» [agudeza compuesta fingida] and notes that, as contemporary censors of the work argued, El Criticón should be seen chiefly as a handbook of (neo-stoic) moral philosophy disguised by the use of allegory to render it amenable and of practical use. As in a fable, where the didactic intent is disguised as a fictional story, the two protagonists of El Criticón are the sapiens and the stultus of neo-stoic philosophy in disguise; their adventures are intended to portray the development of a man aspiring to wisdom, from his beastly beginnings to the quasi-perfection that brings him close to felicity. As his contemporaries observed, in this ambitious mixed-genre work, moral philosophy and courtly philosophy overlay one another in the form of «disguised metaphors».